Unsteady hydrodynamics of tidal turbine blades - Scarlett, Gabriel Thomas (The University of Edinburgh, 2019)
Tidal turbines encounter a range of unsteady flow conditions, some of which may induce severe load fluctuations. A rotor blade can experience stall delay, load hysteresis and dynamic stall. This thesis addresses the need for the quantification of the unsteady flow around and loads on a full-sale tidal turbine rotor to improve fatigue analysis and enable the development of mitigating technologies. A model for the unsteady hydrodynamics of the rotor has been developed which comprises of blade-element momentum, attached flow, separated flow and rotational augmentation implementations. The model can take as an input synthetic flow velocities or measured flow velocities. The code is readily available from the author's GitHub repository (www.github.com/gabscarlett). A parameter study across a range of flow conditions is carried out by modelling the flow and predicting the root bending moment responses. The results show that waves and turbulence are the main sources of unsteadiness, and that extreme waves dominate over extreme turbulence. Severe yaw misalignment increases the load fluctuations but reduces the maximum peak. Large yaw angles, low tip-speed ratios, and very large waves lead to dynamic stall increasing the mean loads. Conversely, added mass effects mostly attenuate the load peaks. An assessment of the rotor's performance during large, yet realistic wave conditions is carried out by considering field measurements of the onset flow. The load cycle is found to be governed by the waves, and the power and blade bending moments oscillate by half of their mean values. While the flow remains attached near the blade tip, dynamic stall occurs near the blade root, resulting in a twofold overshoot of the local lift coefficient compared to the static value. At the optimal tip-speed ratio, the difference between the unsteady loads computed with the proposed model and a simple quasi-steady approximation is small. However, below the optimal tip-speed ratio, dynamic stall may occur over most of the blade, and the maximum peak loads can be twice those predicted with a quasi-steady approximation. These results inform designers of the governing loads which are important for fatigue analysis. This will enhance the durability of tidal turbine blades without over-engineering them. In addition, the results reveal under which conditions simple, low-cost modelling approaches can be applied. These will, in turn, reduce the levelised cost of tidal energy, making the sector more commercially viable.
Keywords: tidal stream turbine; unsteady loadings; unsteady flow conditions; fatigue analysis; blade-element momentum; performance assessment